A Review of Graphene‐Based Electrochemical Microsupercapacitors. Issue 1 (15th November 2013) - Xiong, Guoping; Meng, Chuizhou; Reifenberger, Ronald G.; Irazoqui, Pedro P.; Fisher, Timothy S.
Abstract The rapid development of miniaturized electronic devices has led to a growing need for rechargeable micropower sources with high performance. Among different sources, electrochemical microcapacitors or microsupercapacitors provide higher power density than their counterparts and are gaining increased interest from the research and engineering communities. To date, little work has appeared on the integration of microsupercapacitors onto a chip or flexible substrates. This review provides an overview of research on microsupercapacitors, with particular emphasis on state‐of‐the‐art graphene‐based electrodes and solid‐state devices on both flexible and rigid substrates. The advantages, disadvantages, and performance of graphene‐based microsupercapacitors are summarized and new trends in materials, fabrication and packaging are identified.